12. ANALYSIS OF SOME RISK FACTORS ASSOCIATED WITH DRUG-RESISTANT EPILEPSY IN CHILDREN (Vietnam Journal of Community Medicine, 2024)
Objective: Identify some risk factors for drug-resistant epilepsy in children.Subjects and methods: Cross-sectional descriptive study on 100 children with epilepsy. including 46 females (46%) and 54 males (54%), divided into 2 groups: drug-resistant epilepsy group (n = 50) and drug-responsive epilepsy group (n = 50), diagnostic criteria according to the International Association against Epilepsy (ILAE 2010).Results: Drug-resistant epilepsy with a history of status epilepticus accounted for 30%, neonatal seizures accounted for 22%, febrile seizures accounted for 44%, psychomotor retardation accounted for 92%. The average age of onset in the drug-resistant epilepsy group was 17.3 ± 13 months, the average frequency of seizures per day was 12 ± 8. Generalized epilepsy accounted for 74% of both study groups. There were 18 cases classified as syndrome, accounting for 18%. Paraclinical results of electrostatic discharge and brain MRI were abnormal in drug-resistant and responsive epilepsy groups, accounting for 94% and 30%, respectively. Regression analysis of results: Neonatal seizures, febrile seizures, history of status epilepticus, delayed psychomotor development, abnormal electroencephalogram and MRI are factors related to epilepsy.Conclusion: Patients with a history of neonatal seizures, a history of febrile seizures, a history of status epilepticus, psychomotor retardation, abnormal electroencephalogram and brain MRI are risk factors. associated with drug-resistant epilepsy.
Keywords: Children, epilepsy, drug-resistant epilepsy.